1990
DOI: 10.3382/ps.0692057
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Growth and Plasma Growth Hormone Secretion in Turkeys Selected for Increased Egg Production

Abstract: Male and female turkeys of a slow-growing line selected for increased 180-day egg production (Line E) and its faster growing randombred control (RBC1) were sampled weekly for BW and plasma growth hormone (GH) content. Hatching weights were higher for RBC1 than Line E poults, but no difference was observed between sexes. The pattern of growth of the two lines, as described by the Gompertz equation, was different in magnitude of growth [BW at point of inflection (POI) and asymptote] but not in form (slope and ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Plasma GH in the E line is higher than in its randombred control line at hatching but higher in the randombred control line from Weeks 7 to 28 of growth (Anthony et al, 1990). Eggs from the E line were smaller and contained less solids than those of the RBC2 line.…”
Section: Discussionmentioning
confidence: 88%
“…Plasma GH in the E line is higher than in its randombred control line at hatching but higher in the randombred control line from Weeks 7 to 28 of growth (Anthony et al, 1990). Eggs from the E line were smaller and contained less solids than those of the RBC2 line.…”
Section: Discussionmentioning
confidence: 88%
“…Reduced BW resulting from selection for increased 180-day egg production observed in the current study was consistent with this negative correlation. Anthony et al (1990) reported this reduction in growth as a modification of magnitude rather than form. The shape of die growth curve was the same for RBC1 and me E line birds; however, BW at various points on the growth curve were larger for RBC1.…”
Section: Measurementmentioning
confidence: 90%
“…Vasilatos-Younkin et al (1990) found total hepatic GH binding capacity did not differ between the RBC2 and F lines at 2, 4, 8,14, and 24 wk of age. Plasma GH was higher in Line E than in the RBCl line at hatching but higher in the RBCl line than in Line E from Weeks 7 to 28 (Anthony et al, 1990). Bacon et al (1993) measured plasma concentrations of insulin-like growth factor-I (IGF-I) in the RBC2 and F lines from 1 to 28 wk of age.…”
Section: Hormonal Measurements In the Turkey Linesmentioning
confidence: 99%
“…Reported estimates (Cook et al, 1962;Clayton, 1971;Arthur and Abplanalp, 1975) of the genetic correlation between egg production and BW were low (approximately -0.1). Anthony et al (1990) compared the growth curves of the E and RBC1 lines after 28 generations of selection in the E line. The pattern of growth of the two lines, as described by the Gompertz equation, was different in magnitude of growth (BW at point of inflection and asymptote) but not in form (slope and age at point of inflection and age at asymptote).…”
Section: Direct and Correlated Responses To Selectionmentioning
confidence: 99%